Multiuser MIMO precoding and user scheduling for mobile communications - Tiong, Tiong Teck Chai (2015)
© 2015 IEEE. Long term evolution advanced (LTE-A) mobile wireless communications has adopted multiuser multiple-input multiple-output (MU-MIMO). Precoding is paramount to achieve downlink MU-MIMO capacity. Tomlinson Harashima Precoding (THP) can eliminate inter user interference (IUI) and inter antenna interference (IAI) to achieve lower bit error rate (BER). THP first decompose MU-MIMO into single user MIMO (SU-MIMO) blocks then further decompose into independent single-input single-output (SISO) channels. THP limits the transmitter power to avoid high instantaneous peak transmit power and achieve performance close to Dirty Paper Coding (DPC) but with much lower complexity. User scheduling for transmission select favorable channels to maximize sum rate. Our proposed THP decomposition method with user scheduling outperforms the existing Block Diagonalization (BD) schemes.